Social Cohesion in Frontiers: Case Study of Indonesia-Timor Leste Cross-Border Society - Saehu, Rahmat; Wulandari, Indah (Proceedings International Conference on Education Innovation and Social Science, 2024)
In contrast to Indonesia's borders with Malaysia and Papua New Guinea, the border with Timor Leste has complexities. One line divides the island from north to south, and another includes a small enclave area in the northwest of Timor Island, which is a legacy of colonial occupation by the Dutch to the west of the island and by the Portuguese to the east. After Timor Leste's independence, people on the border had to change how they interacted in the social, political and economic spheres. This article, written using qualitative methods, attempts to describe the dynamic of society on the border of two countries. The research results show that even though politically, Timor Leste and Indonesia are separated into two countries, they are very closely related to each other from a socio-cultural aspect. The people on the border have kinship relations in the two countries and are socially and culturally connected even though they are politically separated as citizens. There are at least three activities involving citizens of two countries. The first is a traditional ritual in their house, which allows citizens of two countries to cross each other to return to their homeland. Second, economic transactions can be carried out legally or illegally. Third, they often do unofficial international sports representing villages directly adjacent to national borders.